Metastatic breast tumors from extramammary malignancies: a case series - Ryoko Semba; Yoshiya Horimoto; Atsushi Arakawa; Mitsue Saito (Surgical Case Reports)
Abstract Background Metastatic breast tumors from extramammary malignancies are quite rare. Characteristics of such tumors are unclear due to small number of reported cases. During 2012–2019, approximately 3,500 malignant breast tumors were diagnosed with needle biopsy at our hospital and we experienced three cases (0.09%) of metastatic extramammary malignancies. We herein report these cases focused on imaging and pathological findings. Case presentation The first case was a 59-year-old woman who underwent curative surgery for thyroid cancer. After developing lung and ovarian metastases, she visited our department with a mass in her right breast. Ultrasound revealed a 7 mm-sized oval mass. With high depth–width ratio and abundant blood flow, primary breast cancer was suspected. Core needle biopsy revealed atypical cells with nuclear grooves proliferating in papillary formation. With immunohistochemical examination, her final diagnosis was metastatic thyroid cancer. The second case was a 74-year-old woman with metastatic spinal tumors and referred to our department for searching primary tumor. She was diagnosed with gastric cancer at the age of 41. Ultrasound revealed a hypoechoic area including cysts and the internal echo level was uneven. Contrast-enhanced magnetic resonance imaging showed a non-mass lesion with heterogeneous internal enhancement pattern, suggesting ductal carcinoma in situ. Core needle biopsy showed alveolar lesion with predominant signet cell-like morphology. We histologically diagnosed her disease as metastatic gastric cancer. The last case was 33-year woman with Stage IV clear cell sarcoma of the left foot. She came to our department after she felt a lump on her right breast. Ultrasound revealed a 45 mm-sized mass. Her disease was confirmed as metastatic clear cell sarcoma by needle biopsy. Conclusions Imaging suggested malignancies, but it was difficult to distinguish them from primary breast cancer. Our cases indicate that metastatic tumors to the breast might have imaging patterns specific to primary organs, although more cases should be accumulated to establish such patterns on imaging. The first two cases shared some similar pathological findings with breast cancer, but also had some histological characteristics of the primary tumors. Hence, it was possible to diagnose these cases as metastatic tumors with careful observation.